DISCOURSE ANALYSIS: UNCOVERING MEANING AND PRAGMATICS IN TERE LIYENOVELS “PULANG PERGI” - Elyana Feronica Manurung; Rahel Raphita Sinabutar (INJOSEDU: International Journal of Social and Education, 2025)
This article delves into the depths of discourse analysis to uncover the nuanced layers of meaning and pragmatics embedded within Tere Liye's novel "Pulang Pergi". Employing a multidimensional approach, it examines the linguistic structures, contextual implications, and socio-cultural factors at play in the narrative. Through the lens of discourse analysis, the study elucidates how language functions beyond its literal interpretation, shedding light on the intricate interplay between language, society, and culture. Drawing from Tere Liye's distinctive style and narrative techniques, the article explores the thematic motifs, character dynamics, and rhetorical strategies employed in "Pulang Pergi". By dissecting the dialogues, narrative structures, and communicative acts within the novel, it uncovers the underlying ideologies, power dynamics, and social constructs that shape the characters' interactions and the overall narrative trajectory. Moreover, the analysis delves into the pragmatic aspects of language use, examining how speech acts, politeness strategies, and contextual cues contribute to the construction of meaning and interpretation within the text. Through a comprehensive discourse analysis, this article not only provides valuable insights into Tere Liye's literary craftsmanship but also offers a deeper understanding of the socio-cultural context and linguistic intricacies embedded within "Pulang Pergi". It underscores the significance of discourse analysis as a powerful tool for unraveling the complexities of language and literature, illuminating the rich tapestry of meanings and pragmatics woven into literary texts.